Design and comparative study of vertical LEDs with graphene, ITO and Ni/Au as contact/current spreading layer. (3rd January 2018) - Singh, Sumitra; Mahala, Pramila; Pal, Suchandan
Abstract: This work evaluates the effect of graphene, indium tin oxide (ITO) and Ni/Au as contact/current spreading layer/current spreading layer for GaN vertical light emitting diodes (V-LEDs). In this simulation study, the effect of these contact/current spreading layers on different performance parameters of GaN V-LEDs has been studied. By using these three different types of contact/current spreading layers, we have comparatively studied the effect on light extraction efficiency (LEE), optical output power, wall plug efficiency and radiant intensity of V-LEDs. As per the simulation results, it shows that using graphene contact/current spreading layers, it is possible to achieve better performance than using ITO and Ni/Au contact/current spreading layers. For graphene/(Ni/Au) contact/current spreading layers, the LEE is improved by 36.77% whereas for ITO/(Ni/Au) contact/current spreading layers it is improved by 13.74%. Also, by using graphene/(Ni/Au) contact/current spreading layers, the optical output power of LEDs improved by 11.11% whereas for ITO/(Ni/Au) contact/current spreading layers shown 4.16% improvement. The radiant intensity is enhanced by 37.65% for graphene/(Ni/Au) contact/current spreading layers and 13.5% for ITO/(Ni/Au) contact/current spreading layers. In this report, we have given a detailed analysis of the obtained simulation results. The simulation was carried out in SimuLED tool.